Character Building: Sebuah Catatan Reflektif Tentang Anak Usia Dini di Growing PAUD Inklusi Yogyakarta - Suratman, Bayu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This research was conducted at Growing PAUD Inclusion in Yogyakarta where the value assesment process was carried out by the inclusion. The focus of this research is to answer fundamental questions relating to the character education process carried out in Growing PAUD Inclusion Yogyakarta. Inculcation of character to early childhood in Growwing PAUD Inclusion through the learning process carried out by the teacher both from the beginning of entering until returning home from school. This paper departs from a qualitative study in which data is obtained from interviews and direct observations at the Growing PAUD Inclusive research location